A comparative study of the five-repetition sit-to-stand test and the one minute sit-to-stand test to assess exercise tolerance in sarcoidosis patients - Cilekar, Sule; Balci, Aydin; Cosgun, Ibrahim Guven; Gunay, Sibel; Saracli, Sinan; Gunay, Ersin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: In this study, we aimed to investigate the exercise tolerance in Sarcoidosis patients with sit-to-stand method Methods: In our cross-sectional study 49 consecutive Sarcoidosis patients included in the study. Patients with Sarcoidosis performed 5 repeated sit-to-stand, 1 minute sit-to-stand test (1MSTS) and the 6-minute walking test (6MWT). Moreover, we collected pulmonary function test, sarcoidosis stage, treatment status, body max index, quadriceps muscle strength. A receiver operating characteristic curve analysis of the 5STS and 1MSTS results was used to predict 6-minute walk distance (6MWD). We evaluated their feelings about the two end STST modes by Borg dyspnea score. Results: The average age of the patients was 49 ± 19. Four patients had stage 3 sarcoidosis, while the others had stage 1 sarcoidosis. The average 6MWD result of all patients was 410 ± 153 meters. When we looked at the correlations between 5RSTS and 1MSTS in 6MWT, significant correlations were observed (r=0.454, p=0.00) (r=0.373, p=0.08). A significant correlation was observed between 1MRSTS and 5RSTS with quadriceps muscle strength (r=0.677, p=0.00) (r=0.48, p=0.00). Conclusions: Based on the results of our study, 1MSTS, 5RSTS, and 6MWT have similar correlations. Both are reasonable tests that can replace the 6MWT in sarcoidosis patients. As a primary screening test for predicting poor 6MWD, the 5STS is similar to the 1MSTS in terms of sensitivity and specificity, but the 5STS provides a better patient experience.